Hyperdominance of Tree Species and Biomass in Mount Gede Pangrango National Park, Indonesia - Andes Hamuraby Rozak; Sri Astutik; Zaenal Mutaqien; Didik Widyatmoko; Endah Sulistyawati (Jurnal Ilmu Kehutanan)
The hyperdominance of tree species and biomass is a concept explaining the importance of a small portion of species and biomass relative to the average of biomass in a forested area. Understanding this concept has important implication on forest monitoring, especially to monitor the most significant species that show high contributes on biomass and its ecological restoration. Hyperdominance analysis of tree species and large trees (DBH > 50 cm) contribution to tree biomass were investigated in tropical mountain forest of Mount Gede Pangrango National Park (TNGGP). A total of 26 sample plots were installed in 26 different altitude between 1013 and 3010 m asl and grouped into three zones i.e. submontane, montane, and subalpine zones. Trees within plot were identified, measured, and grouped into three groups i.e. small (DBH 5-30 cm), medium (DBH 30-50 cm), and large trees (DBH>50 cm). The result showed that there were hyperdominant in TNGGP. Four species from 114 identified tree species i.e. Schima wallichii, Altingia excelsa, Vaccinium varingiaefolium, and Castanopsis acuminatissima represented 56.96% of the total biomass in the plot level. Furthermore, only 13% of trees from 1471 trees responsible for 61.4% of the total tree biomass in the plot level. However, small and large trees have similar significant contribution to the average biomass in the forest level i.e. 40.9% and 38.77%, respectively. These results suggest that only few species represent a huge amount of biomass. Both small and large trees play important role in the forest biomass of TNGGP.